FIQIH: DARI TRADISIONALISME, PEMBAHARUAN, HINGGA GEOPOLITIK - Marwah, Hasan Basri (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
One of the principal objects of cultural studies based on racial differentiation is Islam as a form of imaginative translation boundary that swept the Western world in general. Jurisprudence (Fiqh) is not just a question of legal manifestation and "punishment" of God  in the world. Fundamentally,  fiqh is one basis of the tradition of classical scholarship Muslims in all places. where there is a group of Muslims evolved historically, the worth in it strongly developed jurisprudence as its base. As a classical discipline / traditionalist, Jurisprudence has layers that must be parsed so as to provide an adequate picture to understand the position, function, and process of formation of Islamic law as the basis of traditional society. For that we need to understand the position and function of jurisprudence in the geopolitical chessboard constellation of general knowledge. The role and function of the Jurist  among Muslims must be understood in terms of their position in the world of Islamic knowledge. Authorities held by the jurists were not only related to the transfer are given and transcendental but an authority established on the mastery of the humanities disciplines, notably linguistics (nah}wu, s}araf, balagha), the science of hadis, tafsir, kaidan fiqh, and others.